Terbentuknya Identitas Fans Sepak Bola sebagai Budaya Massa dalam Industri Media - Syahputra, Iswandi (Informasi, 2016)
Nowadays football is not merely sport. It has become industry, even popular culture. This happen because on the same time mass media grows into mass culture industry. The union of football and mass media as industry has melted few social and culture boundaries. Socially"”through mass media"”football had joined many social background into football fans identity, and it even connect all over the world. Football had transformed into popular culture that always moves in instability that drain its fans's emotion. The football fans emotion in turn polarised into fans club which was created based on imaginary bound. Fans is the most visible part from text society and pop culture practice that could become fanatic. This fans fanatism phenomena could happen because the fans are pasif and patologic victim of mass media. This phenomena also mark the indication of transition from agricultural society into industrial and urban society.